2004
DOI: 10.1158/0008-5472.can-03-0654
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Modeling of Kinetics of Cancer Cell Killing by Doxorubicin and Doxorubicin Encapsulated in Targeted Liposomes

Abstract: Various mathematical approaches have been devised to relate the cytotoxic effect of drugs in cell culture to the drug concentration added to the cell culture medium. Such approaches can satisfactorily account for drug response when the drugs are free in solution, but the approach becomes problematic when the drug is delivered in a drug delivery system, such as a liposome. To address this problem, we have developed a simple model that assumes that the cytotoxic potency of a drug is a function of the intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 28 publications
5
142
0
2
Order By: Relevance
“…Liposomes are differentiated from the other types of carriers by following properties: (a) they can easily pass through several biological barriers and also have the ability to protect drugs against destructive reagents and conditions (b) liposome carriers have the ability of targeted delivery [14]. Rom and colleagues demonstrated the increasing therapeutic efficiency of Doxorubicin in liposomal in comparison with standard form on melanoma cell lines [23].…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes are differentiated from the other types of carriers by following properties: (a) they can easily pass through several biological barriers and also have the ability to protect drugs against destructive reagents and conditions (b) liposome carriers have the ability of targeted delivery [14]. Rom and colleagues demonstrated the increasing therapeutic efficiency of Doxorubicin in liposomal in comparison with standard form on melanoma cell lines [23].…”
Section: Discussionmentioning
confidence: 99%
“…56,57) Huang and coworkers demonstrated that a PEGylated liposome-polycation-dNA nanoparticle (LPD) modified with anisamide on top of PEG efficiently delivered siRNA to lung carcinomas with high expression levels of sigma receptors, which resulted in luciferase gene silencing in metastatic tumors compared with nontargeted PEGylated LPd. 58,59) Antibodies have been widely investigated as ligands for the tumor targeting of liposomes due to their high specificity and affinity for target molecules.…”
Section: -28)mentioning
confidence: 99%
“…Liposomes (nanosized phospholipid vesicles) bearing oligosaccharide HA conjugated to a phosphatidylethanolamine lipid have been used as a targeted drug carrier for doxorubicin. 37,38,41,69,70 Two different approaches to attach HA to liposomes were developed. 41,75 In the earliest report, HMW-HA was coupled via the glucuronic carboxylate to phosphatidylethanolamine in pre-formed liposomes.…”
Section: C Hyaluronan In a Targeted Nanocarrier Systemmentioning
confidence: 99%
“…Pharmacokinetic properties, such as circulation time and biodistribution, are influenced by incorporating the targeting and cellspecific uptake properties of HA onto large carriers. Cargos delivered to CD44 over-expressing cells include anti-cancer drugs: epirubicin, 14 doxorubicin, 37,38,41,69,70,71 paclitaxel, 28,29,62,63 and mitomycin c, 14,70 as well as agents such as siRNA, 72 iron oxide magnetic particles, 73 and DNA. 74 These studies are summarized in Tables 3 and 4. Several different methods have been used to improve the distribution of doxorubicin, which has significant cardiotoxicity as a free drug.…”
Section: C Hyaluronan In a Targeted Nanocarrier Systemmentioning
confidence: 99%